Open Up – the Mission Statement of the Control of Impulsive Action (Ctrl-ImpAct) Lab on Open Science - Christina B. Reimer; Zhang Chen; Carsten Bundt; Charlotte Eben; Raquel E. London; Sirarpi Vardanian (Psychologica Belgica, 2019)
The present paper is the mission statement of the Control of Impulsive Action (Ctrl-ImpAct) Lab regarding Open Science. As early-career researchers (ECRs) in the lab, we first state our personal motivation to conduct research based on the principles of Open Science. We then describe how we incorporate four specific Open Science practices (i.e., Open Methodology, Open Data, Open Source, and Open Access) into our scientific workflow. In more detail, we explain how Open Science practices are embedded into the so-called ‘co-pilot’ system in our lab. The ‘co-pilot’ researcher is involved in all tasks of the ‘pilot’ researcher, that is designing a study, double-checking experimental and data analysis scripts, as well as writing the manuscript. The lab has set up this co-pilot system to increase transparency, reduce potential errors that could occur during the entire workflow, and to intensify collaborations between lab members. Finally, we discuss potential solutions for general problems that could arise when practicing Open Science.